THE EFFECTIVENESS OF TRAUMATIC COUNSELING TO REDUCE INNER CHILD TRAUMA IN FEMALE STUDENTS OF PGRI ARGOPURO JEMBER - Agustin, Ica Dwi; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Journal of English Language and Education, 2025)
This study investigates the effectiveness of traumatic counseling in reducing inner child trauma among female students at Universitas PGRI Argopuro Jember. Negative childhood experiences can lead to unresolved trauma that impacts adult behavior and mental well-being, hindering academic and personal growth. The research employed a quantitative approach with a one-group pretest-posttest quasi-experimental design. A purposive sample of six female students with moderate to high inner child trauma was selected. Data was collected using a validated inner child trauma questionnaire and analyzed with a paired-sample t-test. The intervention consisted of six sessions incorporating writing therapy and a multicultural approach. The results showed a significant reduction in trauma scores from pretest to posttest (p0.05), indicating the counseling's high effectiveness. The intervention was particularly successful in improving emotional regulation, self-worth, and reducing feelings of guilt. These findings suggest that this integrated counseling model is a viable and effective method for addressing inner child trauma in university students.